PENDIDIKAN, PELATIHAN DAN KINERJA - ', Khudriani (Jurnal Ilmu Administrasi Negara, 2016)
Education, Training and Performance. This study aims to determine the effect of education and training on employee performance compensation PLP at the University of Riau either simultaneously or partially. PLP employee study population of 50 people and the samples taken as many as 25 people with stratified random sampling technique. Data obtained with questionnaires. Data analysis method used is multiple linear regression analysis using SPSS 17. The results showed that the education training significantly influence employee performance Institution educational laboratories compensation whereas no significant influence on employee performance PLP. Education training and compensation together do not significantly affect the performance of employees Institution educational laboratory.